THE EFFECT OF FINANCIAL LITERACY, FINANCIAL INCLUSION, AND FINANCIAL TECHNOLOGY ON THE FINANCIAL PERFORMANCE OF MSMEs - SITI MUNFAQIROH; Rizky Nur Anisah Grafianni; Benita Rachmania (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are considered to play an important role in driving a country's economic growth. The purpose of this study is to determine and analyze the effect of financial literacy, financial inclusion, and financial technology on financial performance. This study is a quantitative descriptive study. The sample size in this study was 71 samples determined using stratified purposive sampling. The data were analyzed using SmartPLS 4. The results of this study indicate that financial literacy has a significant effect on financial performance, financial inclusion does not have a significant effect on financial performance, and financial technology has a significant effect on financial performance.